RANS-VOF modelling of the Wavestar point absorber. (August 2017) - Ransley, E.J.; Greaves, D.M.; Raby, A.; Simmonds, D.; Jakobsen, M.M.; Kramer, M.
Abstract: Numerical modelling has become commonplace in the development of offshore structures, however for dynamic systems such as Wave Energy Convertors (WECs) conventional numerical tools may not be able to capture the full range of behaviours required for engineering analysis. This is particularly problematic in extreme seas where the nonlinearities and coupled nature of these systems become important. In this work a fully nonlinear, coupled tool for simulation of WECs is produced and compare with physical measurements. Regular wave interactions with both a fixed and freely-pitching, 1:10 scale model of the Wavestar are reproduced numerically. The numerical model is shown to be capable of predicting the pressure on the float's surface and the fully coupled motion of the device. However, the results indicate that the higher-order free surface behaviour in the vicinity of the device is not being captured correctly. Finally, the numerical model is shown to cope with an extreme regular wave including large amplitude motion, full submersion and high levels of free surface distortion. The results presented suggest that the quality of the numerical reproduction does not decrease with wave steepness; however the execution time of simulations increases significantly with increased float oscillation. Highlights: A fully nonlinear, coupled model of the Wavestar WEC has been created using open-source CFD software, OpenFOAM ® . The response of the Wavestar WEC is simulated in regular waves with different steepness. Predictions of body motion, surface elevation, fluid velocity, pressure and load are compared with physical measurements. Model stability is shown under extreme motions, green water and break-up of the free surface.